2015
DOI: 10.1111/asj.12443
|View full text |Cite
|
Sign up to set email alerts
|

Change of fatty acid composition of the lumbar longissimus during the final stage of fattening in the Japanese Black cattle

Abstract: Consideration of the shortened fattening period seems to be worthwhile for the realization of profitable beef production. In this study, change of fatty acid composition of the lumbar longissimus during the final stage of fattening was investigated in Japanese Black cattle. Each of 110 fattening animals was sampled three times: the initial two samples were taken by biopsy (25.7 months and 27.5 months on average) and the final one was from carcasses (29.9 months on average). Preliminary analysis indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The animals used in their study were approximately 3 months younger than the animals in our study. Because MUFA is known to be affected by age (Honda et al, 2016), it was suggested that age at slaughter largely contributed to the difference in MUFA between the two studies.…”
Section: Basic Statisticsmentioning
confidence: 99%
“…The animals used in their study were approximately 3 months younger than the animals in our study. Because MUFA is known to be affected by age (Honda et al, 2016), it was suggested that age at slaughter largely contributed to the difference in MUFA between the two studies.…”
Section: Basic Statisticsmentioning
confidence: 99%
“…Intensive feeding and extended finishing time can favorably affect the yield and quality of beef produced. It is important to increase the intensity and method of feeding in the final fattening stage [ 100 ]. The high growth potential of the animal at a young age is inhibited when the animal reaches somatic maturity [ 101 ].…”
Section: Discussionmentioning
confidence: 99%